Assessing the feasibility of using autogenous maxillary bone graft to repair isolated orbital floor fractures: A pilot study using CT measurements. (8th June 2022) - Yu, Stephen; De Silva, Harsha; Narsinh, Pritesh; Marra, Jamie; Fong, Amy; Dias, George
Abstract: Introduction: Orbital floor fractures are a common injury managed by oral maxillofacial surgeons. They can result in significant bony defects that increase the orbital volume and necessitate surgical repair to avoid the development of enophthalmos. A variety of materials have been used in the reconstruction of orbits including alloplastic materials and autogenous bone grafts. The use of the anterior maxillary antral wall as a bone graft offers the advantage of being readily accessible, naturally thin and has less donor site morbidity than other bone graft sites. There is a paucity of literature in regards to how and when to use an anterior maxillary antral wall graft. Materials and Methods: We performed a retrospective review of computerized tomography head scans for patients presenting with isolated orbital floor fractures over a 5‐year period. 25 patients were included in the study and manual measurements were recorded for the orbital floor defect and the dimensions of the ipsilateral and contralateral anterior maxillary wall. Results: It was found that 92% of fractures could have been repaired using a contralateral anterior maxillary wall bone graft ( p < 0.05). Conclusion: Use of the anterior wall of the maxillary antrum is a feasible alternative to traditional alloplastic materials. Further study using three‐dimensional bio‐modelling could help developing more accurate guidelines for using this technique in orbital fracture repair.